PENGARUH ELEMEN TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DI INDONESIA (Studi Empiris pada Perusahaan yang Terdaftar dalam Indeks Kompas 100 di Indonesia Tahun 2019-2021) - Maharani, Azusma; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2024)
This study examines several corporate governance characteristics on corporate social responsibility (CSR) disclosure in the context of emerging markets in 2019-2021. The researcher used annual report data of companies listed in the KOMPAS 100 index from 2019-2021 to investigate the relationship between board independence, board size, foreign ownership, and government ownership on the level of CSR information reporting using the ESG disclosure score. Panel data regression analysis which includes three techniques namely Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), was used to analyze the data in this study. The Random Effect Model (REM) shows the best fit among these models. The results show that board independence, board size, and government ownership show a significant and positively correlated relationship with the company's decision to disclose CSR information. In contrast, foreign ownership is an insignificant relationship with the company's decision to disclose CSR information. This study extends the literature on CSR information, especially in developing countries where the government plays a vital role in driving economic development. Thus, the results can provide insights to policymakers to identify corporate governance characteristics that encourage CSR reporting in Indonesian listed companies.This study aims to fill a crucial gap by examining environmental disclosure in integrated reports in Indonesia. Specifically, this study will investigate corporate governance factors, board size, board independence, board gender diversity, and CSR committee, which are related to environmental disclosure levels in integrated reports in Indonesian companies.